Design of DC Accumulator Charging using Backup Accumulator Based on Inverter and Converter Device - Marpaung, Parlindungan Pandapotan (Politeknik Negeri Semarang, 2022)
The charging of DC accumulator thatexperiences a lack of electric charge energy, usuallyutilizes an AC input power from the PLN network. Whenthe AC input power from the PLN network is unavailable,a DC power source is used from the backup DCaccumulator as a substitute. The research objective is todesign an internal DC accumulator charging using abackup DC accumulator equipment based on inverterand converter equipment. The charging system will useinput power from the backup DC accumulator to replacethe AC input power from the PLN network. The electricvoltage of the internal DC accumulator that is filled(charged) is the initial condition of VDC(Acu.Int.)= 8.76 Voltsuntil it reaches the normal condition of 12.05 Volts with acapacity of charging current of 5 Ah (Ampere.hours)absorbs electrical energy of W(Acu.Int.) = 16.45 Wh(Watt.hours). The results show that the equipment supplya DC charger of 13.0 volts and PDCof 21.32 watts to theinternal DC accumulator. The comparison of W(Acu.Int.) to PDC produces time charging, t(charging)of 46.29 minutes